Novejša sodna praksa VS RS na področju delovnih razmerij - Debelak, Marijan (Delavci in delodajalci, 2019)
Following the introductory presentation of two procedural novelties before the Supreme Court of the RS, the author presents some examples of recent case law of the Supreme Court of the Republic of Slovenia in individual labour disputes. These examples are presented by individual institutes of labour law: the existence of an employment relationship, mobbing at work, leading and managerial staff, and the termination of employment contract, judicial dissolution of a contract, overtime work, seniority bonus and interpretation of collective agreements. Particularly interesting is the development of case law in cases of mobbing, (e.g. when setting up a claim for damages), of management and managerial staff, the possibility of compensating overtime hours after the end of the reference period, the payment of such hours and the possibility of determining seniority bonus only for the last employer.
Keywords: case law; dodatek za delovno dobo; existence of an employment relationship; interpretation of collective agreements; leading and managerial staff; mobbing; nadurno delo; obstoj delovnega razmerja; odpoved pogodbe o zaposlitvi; overtime work; razlaga kolektivnih pogodb; seniority bonus; sodna praksa; termination of employment contract; trpinčenje; vodilni in poslovodni delavci